Work Family Conflict dan Subjective Well Being Ibu Bekerja di Kampus - Okfrima, Ria; Apriliani, Fitri; Situmorang, Nina Z; Diponegoro, AM (Journal of Economics and Management Scienties, 2024)
Someone who has a high subjective well-being shows a positive condition for an event such as welfare, satisfaction, optimism, hope, and spirituality. This high subjective well-being should be owned by a mother, especially working mothers because individuals who have high subjective well-being will have positive stress management and better physical health. However, some research results show that working mothers have low subjective well-being. This is because work-family conflict usually occurs when domestic life clashes with responsibilities at work, such as getting to work on time, completing daily tasks, or working overtime. Likewise, the demands of home life prevent a person from making time for his work or career-related activities. This is what underlies researchers conducting research with the aim of looking at the relationship between work family conflict and subjective well-being in working mothers. The method in this research is correlational quantitative. The correlational research method is used to see the relationship between the two variables in this case, namely work family conflict as variable X and subjective well-being as variable Y. Sampling in this study uses purposive sampling technique, namely working mothers who have early childhood (pre-school age). ) amounted to 50 people. The measuring instrument used in this study uses a role conflict scale and a subjective well-being scale. The scale model in this study is a Likert scale. From these results, it can be concluded that there is a relationship between work family conflict and subjective well- being in a negative direction, which means that the higher the work family conflict, the lower the subjective well- being and vice versa for working mothers.